2019
DOI: 10.1111/aje.12682
|View full text |Cite
|
Sign up to set email alerts
|

Floral species richness, structural diversity and conservation value of vanilla agroecosystems in Madagascar

Abstract: Agricultural landscapes provide financial livelihoods for farming communities in rural areas. However, such agroenvironments can significantly impact the local floral biodiversity and introduce harmful invasive species to the ecosystem. Despite the prominence of plantations throughout the tropics, their effects on local flora are limited to only a few specific cash crops and geographical regions. Here, we compared the species richness and structural diversity of vegetation in natural forest fragments and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 54 publications
2
25
1
Order By: Relevance
“…The conservation value of vanilla agroforestry can, however, only be assessed relative to other land uses, and, most importantly, in comparison to the land use the agroforest was derived from. This important distinction lacks in previous studies (Hending et al, 2018(Hending et al, , 2019.…”
Section: Vanilla Agroforests As a Conservation Opportunity?mentioning
confidence: 81%
See 2 more Smart Citations
“…The conservation value of vanilla agroforestry can, however, only be assessed relative to other land uses, and, most importantly, in comparison to the land use the agroforest was derived from. This important distinction lacks in previous studies (Hending et al, 2018(Hending et al, , 2019.…”
Section: Vanilla Agroforests As a Conservation Opportunity?mentioning
confidence: 81%
“…The lack of ecological research in vanilla agroforests is surprising given our knowledge on the contributions of other agroforests to biodiversity conservation (Bhagwat et al., 2008). The only studies available for vanilla are from a recent rapid biodiversity assessment (Hending, Andrianiaina, Rakotomalala, and Cotton, 2018; Hending, Andrianiaina, Maxfield, Rakotomalala, and Cotton, 2019): The authors reported fewer lemur sightings in vanilla agroforests than in forests and a diverse plant community in traditionally, less intensively managed vanilla agroforests in proximity to forests. Similarly, we find vanilla agroforests to host fewer bird species than old‐growth forest and show that landscape‐scale forest cover is essential for endemic birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within vanilla agroforests, smallholders use small-statured trees as a support for the climbing orchid, while a variety of taller trees form the canopy above (Havkin-Frenkel & Belanger, 2018). Hence, vanilla agroforests comprise a wide range of tree densities and tree canopy cover (Hending et al, 2020). Furthermore, household surveys in northeastern Madagascar found that vanilla agroforests particularly differ in their land-use history: around 30% of agroforests are forest-derived, established by cleaning the understorey, thinning the forest, and planting vanilla under the canopy of the already established trees (Hänke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This definition embraces a broad range of different management schemes with trees and large woody perennials that already existed prior to the agroforest establishment, but also encompasses spontaneous regrowth or actively planted trees or other tall woody plants (Schroth et al, 2004;Bhagwat et al, 2008). Recent studies show that vanilla agroforests can provide habitat for native wildlife (Hending et al, 2018;Hending et al, 2020;Martin et al, 2021), but it remains unclear to what extent the habitat structure and tree diversity are determined by land-use history.…”
Section: Introductionmentioning
confidence: 99%